Phenotypic profiling of human induced regulatory T cells at early differentiation : insights into distinct immunosuppressive potential - Kattelus, Roosa; Starskaia, Inna; Lindén, Markus; Batkulwar, Kedar; Pietilä, Sami; Moulder, Robert; Marson, Alexander; Rasool, Omid; Suomi, Tomi; Elo, Laura L.; Lahesmaa, Riitta; Buchacher, Tanja (SPRINGER BASEL AG, 2025)
Regulatory T cells (Tregs) play a key role in suppressing systemic effector immune responses, thereby preventing autoimmune diseases but also potentially contributing to tumor progression. Thus, there is great interest in clinically manipulating Tregs, but the precise mechanisms governing in vitro-induced Treg (iTreg) differentiation are not yet fully understood. Here, we used multiparametric mass cytometry to phenotypically profile human iTregs during the early stages of in vitro differentiation at single-cell level. A panel of 25 metal-conjugated antibodies specific to markers associated with human Tregs was used to characterize these immunomodulatory cells. We found that iTregs highly express the transcription factor FOXP3, as well as characteristic Treg-associated surface markers (e.g. CD25, PD1, CD137, CCR4, CCR7, CXCR3, and CD103). Expression of co-inhibitory factors (e.g. TIM3, LAG3, and TIGIT) increased slightly at late stages of iTreg differentiation. Further, CD103 was upregulated on a subpopulation of iTregs with greater suppressive capacity than their CD103− counterparts. Using mass-spectrometry-based proteomics, we showed that sorted CD103+ iTregs express factors associated with immunosuppression. Overall, our study highlights that during early stages of differentiation, iTregs resemble memory-like Treg features with immunosuppressive activity, and provides opportunities for further investigation into the molecular mechanisms underlying Treg function.